2022
DOI: 10.1111/1365-2664.14249
|View full text |Cite
|
Sign up to set email alerts
|

Activity of forest specialist bats decreases towards wind turbines at forest sites

Abstract: Worldwide, wind turbines are increasingly being built at forest sites to meet the goals of national climate strategies. Yet, the impact on biodiversity is barely understood. Bats may be heavily affected by wind turbines in forests, because many species depend on forest ecosystems for roosting and hunting and can experience high fatality rates at wind turbines. We performed acoustic surveys in 24 temperate forests in the low mountain ranges of Central Germany to monitor changes in the acoustic activity of bats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 64 publications
3
12
0
Order By: Relevance
“…Gaultier et al (2023) and Ellerbrok et al (2022) both monitored bats at wind parks in European forested landscapes in the same period as this study and found similar avoidance effects; Myotis spp. activity was more likely to be recorded further from turbines.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Gaultier et al (2023) and Ellerbrok et al (2022) both monitored bats at wind parks in European forested landscapes in the same period as this study and found similar avoidance effects; Myotis spp. activity was more likely to be recorded further from turbines.…”
Section: Discussionsupporting
confidence: 70%
“…Habitat fragmentation and degradation could also explain avoidance effects (Lesiński 2007, Barré et al 2018, especially if turbine development causes insect declines and subsequently reduces foraging habitat (Rydell et al 2010b, Millon et al 2015. Gaultier et al (2023) and Ellerbrok et al (2022) both monitored bats at wind parks in European forested landscapes in the same period as this study and found similar avoidance effects; Myotis spp. activity was more likely to be recorded further from turbines.…”
Section: Avoidance Effects and Fatal Attractionssupporting
confidence: 59%
See 1 more Smart Citation
“…A similar decrease was observed for open-space- and narrow-space-foraging bats at wind turbines in forests (Ellerbrok et al. 2022 , Gaultier et al. 2023 , McKay et al.…”
Section: Impact Of Wind Energy Production On Batssupporting
confidence: 67%
“…Deforestation can affect forest-dependent bat species, which may lose both foraging and roosting habitats (Ellerbrok et al. 2022 , Reusch et al. 2023 ).…”
Section: Impact Of Wind Energy Production On Batsmentioning
confidence: 99%